Correlation Between Sleep Hygiene And Sleep Quality In Patients With Coronary Heart Diseases - Hasibuan, Mujahidah; Dewi, Wan Nishfa; Fitri, Aminatul (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2022)
Introduction: Patients with coronary heart disease (CHD) often experience disturbances in the quality and quantity of sleep. One of the efforts to improve the sleep quality of CHD patients is sleeping cycle management, such as sleep hygiene. This study aims to analyse the relationship between sleep hygiene and sleep quality in patients with coronary heart disease. Methods: This study used the correlation analytic method with a cross-sectional approach. There 72 respondents were involved and selected using a purposive sampling technique based on inclusion criteria. The instruments used to collect data were the SHI (Sleep Hygiene Index) and PSQI (Pittsburgh Sleep Quality Index) questionnaires, which have been tested for validity and reliability. Data analysis used for statistical analysis was the Spearman test. Results: Demographic data depicts that most respondents are the average age of 45-60 years (79.2%), and more than half of respondents were men (69.4%). Data on sleep hygiene showed that good was (31.9%) and moderate was (52.8%). Furthermore, the sleep quality of patients with cardiovascular disease is primarily poor (63.9%). Regarding the analysis of the correlation between sleep hygiene and sleep quality in patients with coronary heart disease, it showed that there is a significant relationship with a p-value of 0.000 and a coefficient of 0.793. It means that the two variables have an intense relationship. Conclusion: Sleep hygiene practice is one of the non-pharmacological solutions for patients with cardiovascular diseases who have sleep disturbance problems. Implementing sleep hygiene practices can improve the quality of sleep for patients and optimally improve health.